TRANSFORMASI MANAJEMEN PEMERINTAHAN DI KABUPATEN SUKABUMI - Agustinus Widanarto (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
ABSTRACT This study is entitled “Government Management Transformation in Sukabumi Regency.” This study is set either by Local Governments or public having not understanding of Regency Sukabumi problems and conditions in terms of geographic, demographic, administrative, economic, and social conditions. This study is designed to know how government management transformation in the dimensions of reframing, restructuring, revitalization, and renewal in Sukabumi Regency. This study was conducted by using a descriptive method and qualitative approach. Informant involved in this study using purposive technique comprises Deputy Regent of Sukabumi, Assistant Chairman of Assembly at provincial level, Chief Executive of Agency for Regional Development, Chief Executive of Living Space Management Agency, Head of Educational Department, Head of Health Department, Head of Housing, Layout, and Cleanliness Agency, and Legal Administrative Section Head ofSukabumi Regency Secretariat. The results of the study showed that there was change in the dimension of reframing, an increase in local vision of 2016 by Regent of Sukabumi turnover. Second dimension is restructuring taking place in dynamic fashion fit the current development of Sukabumi Regency; however, Sukabumi Regency could not to delivery public services. In the third dimension, revitalization, some matter was made but it is not accompanied by adequate change in regulation. While in the fourth dimension, renewal, it is not all of them are put in good run in relation to whole physical condition. There is less education in social sector for human resources development; i.e., public service. In conclusion, under this study, the management transformation was made, but not maximal, in terms of reframing, restructuring, revitalization, and renewal in Sukabumi Regency. Keywords: Transformation, Government Management.